Environmental forensics: a multi-catchment approach to detect origin of sediment featuring two pilot projects in Malaysia - Annammala, Kogila Vani; Nainar, Anand; Mohd Yusoff, Abdul Rahim; Yusop, Zulkifli; Bidin, Kawi; Dominic Walsh, Rory Peter; H. Blake, William; Abdullah, Faizuan; Sugumaran, Dhinesh; Gopal Pillay, Khuneswari (Emerald, 2019)
Although there have been extensive studies on the hydrological and erosional impacts of logging, relatively little is known about the impacts of conversion into agricultural plantation (namely rubber and oil palm). Furthermore, studies on morphological impacts, sediment-bound chemistry and forensic attribution of deposited sediment to their respective sources are scarcer. This chapter introduces the potential for using the multi-proxy sediment fingerprinting technique in this context. Featuring pilot projects in two major floodprone river systems in Malaysia, the studies explore application of geochemistry-based sediment source ascription. The geochemical signatures of sediment mixtures on floodplains were compared to sediments from upstream source tributaries. The tributaries were hypothesised to have different geochemical signatures in response to dominant land management. The first case study took place in the Segama River system (4,023 km2 ) of Sabah, Malaysian Borneo where a mixture of primary forest, logged-forests